Removal of a combination of endocrine disruptors from aqueous systems by seedlings of radish and ryegrass - Gattullo, C.Eliana; Barboza Cunha, Bruno; Rosa, André H.; Loffredo, Elisabetta (Taylor & Francis, 2013)
Endocrine disruptors (EDs) are widespread in the environment, especially aquatic systems, and cause dangerous effects on wildlife and humans. This work was aimed to assess the capacity of radish (Raphanus sativus L.) and ryegrass (Lolium perenne L.) seedlings to tolerate and remove two combinations of EDs containing bisphenol A (BPA), 17α-ethynilestradiol (EE2), and linuron from four aqueous media: distilled water, a solution of natural organic matter (NOM), a lake water and a river water. Seeds of the two species were germinated in each contaminated medium and, at the end of germination, the seedling growth was evaluated by biometric measurements and residual EDs were quantified by chromatographic analysis. Biometric measurements revealed that the phytotoxicity of the two combinations of EDs depended on the medium used. Radish showed a discrete tolerance in distilled water and lake water but was inhibited in the solution of NOM and river water. Ryegrass was negatively affected mainly in river water. The concentration of each ED appeared significantly reduced in all media in the presence of seedlings of both species, but not in the blanks without plants. In 5 days, radish removed up to 88% of BPA, 100% of EE2 and 42% of linuron, and in 6 days ryegrass removed up to 92% of BPA, 74% of EE2 and 16% of linuron. The considerable removal capacity of radish and ryegrass in all media tested encourages the use of phytoremediation to remove EDs from waters. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: 17α-ethynilestradiol; bisphenol A; freshwater; linuron; phytoremediation